2011
DOI: 10.1021/jp206379h
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Microspheres Based on α-Ni(OH)2 Nanosheets Intercalated with Different Anions: Synthesis, Anion Exchange, and Effect of Intercalated Anions on Electrochemical Capacitance

Abstract: Metal oxides and metal hydroxides are interesting, low cost, and low toxicity energy storage materials for electrochemical capacitor applications. Many studies to date have been directed toward replacing RuO 2 1,2 with NiO, 3,4 Co 3 O 4 , 5 MnO 2 , 6 Co(OH) 2 , 7 or Ni(OH) 2 . 8 In recent years Ni(OH) 2 has received much attention due to its superior theoretical electrochemical properties. In particular, β-Ni(OH) 2 has been extensively studied. Despite being a metastable phase, α-Ni(OH) 2 presents itself as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
157
5

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(174 citation statements)
references
References 42 publications
10
157
5
Order By: Relevance
“…Furthermore, two broad and asymmetric peaks are observed at about 33.7 and 60.0°, corresponding to nonbasal spacing and which are present in turbostratic materials. 8 This turbostratic behavior has also been observed in other A-Ni(OH) 2 .…”
Section: Resultssupporting
confidence: 65%
“…Furthermore, two broad and asymmetric peaks are observed at about 33.7 and 60.0°, corresponding to nonbasal spacing and which are present in turbostratic materials. 8 This turbostratic behavior has also been observed in other A-Ni(OH) 2 .…”
Section: Resultssupporting
confidence: 65%
“…(i) Surfactant-intercalated α-derivative structures α-Ni(OH) 2 -like materials in which the intercalated water is replaced with surfactant molecules have been prepared using cetyltrimethylammonium bromide [100], dodecyl sulfate [82,92,[100][101][102][103][104][105][106], dodecylbenzene sulfonate [103], p-aminobenzoate [18] and Tween 80 [100]. The polar or ionic regions of the surfactant molecules interact with the Ni(OH) 2 sheets and the non-polar regions fill the interlayer space.…”
Section: (C) α-Derivative Structuresmentioning
confidence: 99%
“…The γ-NiOOH and β-NiOOH are the corresponding oxidized forms with oxidation states of +3.5 and +3.0, respectively. The α-to-γ transition has attracted quite attention in the recent years due its greater charge exchange (433 [2] vs 289 mA h g −1 of β-to-β [3]). Unfortunately, the α-form has an inherent instability and eventually converts to the β-form [4].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, α-Ni(OH) 2 was prepared following a surfactant-assisted method to control the interlayer spacing and to exchange the intercalating anions [3]. The cyclic voltammetry results demonstrated that the largest specific capacitance was obtained for the chloride-intercalated products (805 F g −1 ), while the smallest value was obtained for the sulfate-intercalated case (221 F g −1 ) [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation